Artists of Cologne. - Spirit Square Center for the Arts, Charlotte; Nexus Contemporary Art Center, Atlanta (Charlotte : Spirit Square - Center for the Arts, 1992)
Beyelschmidt, Rosy ; Fuchs, Harald ; Henning, Reinhard ; Horky, Ulla ; Paulsen, Renate ; Schüler, Manfred ; Tralau, Marianne
Artists of Cologne, Spirit Square Center for the Arts, Charlotte, November 6 - December 31, 1992 / Nexus Contemporary Art Center, January 23 - February 28, 1993
boek